Saving the soul of Georgia : Donald L. Hollowell and the struggle for civil rights - Daniels, Maurice Charles, 1952- (University of Georgia Press, 2013)
"Donald L. Hollowell was Georgia's chief civil rights attorney during the 1950s and 1960s. In this role he defended African American men accused or convicted of capital crimes in a racially hostile legal system, represented movement activists arrested for their civil rights work, and fought to undermine the laws that maintained state-sanctioned racial discrimination. In Saving the Soul of Georgia, Maurice C. Daniels tells the story of this behind the- scenes yet highly influential civil rights lawyer who defended the rights of blacks and advanced the cause of social justice in the United States. Hollowell grew up in Kansas somewhat insulated from the harsh conditions imposed by Jim Crow laws throughout the South. As a young man he served as a Buffalo Soldier in the legendary Tenth Cavalry, but it wasn't until after he fought in World War II that he determined to become a civil rights attorney. The war was an eye-opener, as Hollowell experienced the cruel discrimination of racist segregationist policies. The irony of defending freedom abroad for the sake of preserving Jim Crow laws at home steeled his resolve to fight for civil rights upon returning from war. From his legal work in the case of Hamilton E. Holmes and Charlayne Hunter that desegregated the University of Georgia to his defense of Dr. Martin Luther King Jr. to his collaboration with Thurgood Marshall and his service as the NAACP's chief counsel in Georgia, Saving the Soul of Georgia explores the intersections of Hollowell's work with the larger civil rights movement"--